Multitheoretical Communication Framework of Slang Language: A Case Study toward Interpretation and The Use of Anjay in Indonesia - Arina Rohmatul Hidayah (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This research was conducted with the aim of discussing an issue that is currently viral on social media in Indonesia, namely the prohibition of using the word of anjay as slang language. The lack of research based on theoretical exploration of slang is a component that needs to be completed. So in this case, the researcher puts forward a multitheoretical framework, especially with regard to communication theories, where one of the components of the study also involves problems of language, structure and function in society. Through the case study method, the researcher selected 5 informants who understood and had used the word of anjay. Finally, with in-depth interview, there are many aspects that can be explored from the word of anjay and there are several relevant theories to explain these aspects.